Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 26005 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Lithobates catesbeianus (Shaw, 1802)" ] } The dataset includes 26005 records from 128 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0000242-150831095807960/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences